Maximal intermittent handgrip strategy: design and evaluation of an exercise protocol and a grip tool - Bentley DC (Dove Medical Press, 2016)
Danielle Christine Bentley, Scott Gordon Thomas Faculty of Kinesiology and Physical Education, University of Toronto, Toronto, Ontario, Canada Abstract: Handgrip (HG) exercise has been prescribed as a lifestyle intervention to successfully reduce resting blood pressure (BP) among heterogeneous groups of participants. Current HG protocols have limited accessibility due to complicated exercise prescriptions and sophisticated required equipment. Therefore, this research describes the design and evaluation of the maximal intermittent (MINT) HG exercise strategy, consisting of both a novel exercise protocol (32×5 seconds maximal grip squeezes separated by 5 seconds of rest between sets) and an original grip tool. This research was a multistep progressive design that included 51 postmenopausal women as participants in three separate research studies. Part 1 of this research focuses on the MINT exercise protocol. A literature-informed rationale for the design of the protocol is described. This includes exercise intensity, work-to-rest ratio, and total exercise duration with reference to the unique physiology (mechanoreflex and metaboreflex) of postmenopausal women. Subsequent experimental analyses of acute responses to the MINT protocol revealed that women produced 50% of their maximum grip force with moderate cardiovascular responses (increases of systolic BP: 41.6 mmHg, diastolic BP: 20.1 mmHg, heart rate: 35.1 bpm) that remained far below the thresholds of concern identified by the American College of Sports Medicine. Part 2 of this research describes the creation of a novel grip tool, beginning with a mixed-methods assessment of participant opinions regarding two distinct in-laboratory grip tools, leading to the creation of four prototype MINT tools. Structured focus groups revealed a strong preference for MINT prototype 1 for all tool design features, including color, shape, size, and foam grip. Collectively, the result of this multistep research is a novel HG exercise strategy with enhanced accessibility by being easy to understand and simple to execute. The long-term training effectiveness of MINT as an exercise intervention for the reduction of resting BP has yet to be determined. Keywords: handgrip exercise, blood pressure, new product development, novel exercise strategy, postmenopausal women, exercise safety